Neutrophil-to-lymphocyte ratio: an inflammation marker related to cardiovascular risk in children - Prats-Puig, Anna; Gispert-Saüch, Montserrat; Díaz-Roldán, Ferran; Carreras-Badosa, Gemma; Osiniri, Inés; Planella-Colomer, Montserrat; Mayol, Lluís; de Zegher, Francis; Ibánez, Lourdes; Bassols, Judit; López-Bermejo, Abel (Thrombosis and Haemostasis, 2015)
Low-grade chronic inflammation plays a pathogenic role in cardiovascular disease. An increase in the ratio of circulating neutrophils to lymphocytes (N/L ratio) may serve as a marker of cardiovascular risk in adults. It was the study objective to study whether N/L ratio associates with vascular parameters in children. Subjects were 501 prepubertal and early pubertal Caucasian children (mean age 8.0 years; mean body mass index (BMI) Z-score 0.2 ± 0.9; 266 boys and 235 girls) recruited within an ongoing population-based study. The subjects were stratified into three groups according to age. Neutrophil, lymphocyte, BMI, waist circumference, systolic blood pressure (SBP) and carotid intima-media thickness (cIMT), assessed in all children. The N/L ratio, derived from the absolute neutrophil and lymphocyte counts. In children aged < 7 years (n=190, all prepubertal), no associations were observed between N/L ratio and either anthropometric or cardiovascular parameters. In children aged 7–9 years (n=171, 1.7 % early pubertal), higher N/L ratio associated with higher BMI Z-score and waist circumference (p=0.008 to p< 0.0001). In children aged > 9 years (n=140, 29.2 % early pubertal), N/L ratio associated again with BMI Z-score and waist circumference and also positively with SBP and cIMT (all p=0.008 to p< 0.0001). These associations remained significant in linear regression models following adjustment for possible confounding variables such as age, gender, fasting triglycerides, C-reactive protein and puberty (and for SBP and cIMT, adjustment also for BMI). In conclusion, our results provide the first evidence that a higher N/L ratio is associated with a less favourable cardiovascular profile in children and delineate the development of these associations from late childhood onwards.
Keywords: Body mass index; cardiovascular risk; children; intima-media thickness; neutrophils to lymphocytes ratio